1993
DOI: 10.1073/pnas.90.23.10927
|View full text |Cite
|
Sign up to set email alerts
|

Different perceptual tasks performed with the same visual stimulus attribute activate different regions of the human brain: a positron emission tomography study.

Abstract: To investigate the processing of visual form in human cerebral cortex, we used the PET (positron emission tomography) activation technique to compare the human brain regions that are involved in a visual detection task and two orientation discrimination tasks: the temporal same-different (TSD) task, which includes a short-term memory component, and the identification (ID) task, which is without this component. As a control task we used passive viewing. Stimuli were identical in all four tasks. Subtraction of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
38
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 34 publications
9
38
0
Order By: Relevance
“…First, they provide support to the idea of functional specialization in the human visual system, in line with anatomophysiological evidence from the animal literature-in particular, primate neurophysiology. The activation for orientation in the right superior occipital gyrus of Dupont et al (6), which has been recently replicated in another study from the same group (7), is at a different location from other extrastriate regions activated by different sets of stimuli. For instance, random arrays of moving dots have consistently activated in different laboratories a region at the temporo-occipitalparietal junction, which is thought to be analogous to the motion-specific area MT or V5 in monkey (8).…”
Section: Studies Of Vision and Attentionmentioning
confidence: 78%
See 1 more Smart Citation
“…First, they provide support to the idea of functional specialization in the human visual system, in line with anatomophysiological evidence from the animal literature-in particular, primate neurophysiology. The activation for orientation in the right superior occipital gyrus of Dupont et al (6), which has been recently replicated in another study from the same group (7), is at a different location from other extrastriate regions activated by different sets of stimuli. For instance, random arrays of moving dots have consistently activated in different laboratories a region at the temporo-occipitalparietal junction, which is thought to be analogous to the motion-specific area MT or V5 in monkey (8).…”
Section: Studies Of Vision and Attentionmentioning
confidence: 78%
“…The study of Dupont et al (6) in this issue represents an excellent example of this top-down approach with PET. In all scans, subjects viewed the same set of oriented stationary gratings.…”
Section: Studies Of Vision and Attentionmentioning
confidence: 99%
“…When PFC activation is seen at all, it is most often centered in Broca's area, more ventral PFC areas, and/or around premotor cortex and supplementary motor areas (see, e.g., Awh et al, 1996;Dupont et al, 1993;Jonides et al, 1993;Rowe, Toni, Josephs, Frackowiak, & Passingham, 2000;6 Smith, Jonides, & Koeppe, 1996;Smith et al, 1995).…”
Section: Human Researchmentioning
confidence: 99%
“…Functional imaging studies can access this network level and have shown modulation of sensory responses by attention 32 or by the task. [33][34] Unfortunately, in humans the anatomical connections are largely unknown, making interpretation difficult. Finally, there is the potential using FIN and ACS to measure and locate the origins of top-down influences which also likely vary in task-dependent ways.…”
Section: Future Approachesmentioning
confidence: 99%